Changes in Polyphenol Oxidase Activity During Rooting of Hardwood Cuttings in Three Grape Rootstocks Under Indian Conditions - Satisha, J.; Raveendran, P.; Rokade, N.D. (South African Journal of Enology and Viticulture, 2016)
Polyphenol oxidase (PPO) activity was investigated during rooting in cuttings from the rootstocks Dog ridge, 110 R and St. George, belonging to different Vitis species. Enzyme activity and rooting ability were analysed. Significant differences were found in PPO activity among different rootstocks, with Dog ridge and 110 R having the highest PPO activity during the initial period of planting, followed by a decrease in enzyme activity. In St. George, the enzyme activity was least during the initial periods, but it increased throughout the experiment. The initiation of rooting primordia was observed until 60 to 90 days after planting in Dog ridge and 110 R rootstocks, while it was observed 120 days after planting in St. George, suggesting differences in the rooting behaviour of the rootstocks. The status of various biochemical components of the mother vines, such as total phenols, reducing sugars, carbohydrates, nitrogen, C:N ratio, etc. were analysed to investigate the influence of these constituents on the rooting ability of the rootstocks apart from PPO activity.